THE SOUTH AFRICAN DEFENCE FORCE AND OPERATION HOOPER, SOUTHEAST ANGOLA, DECEMBER 1987 TO MARCH 1988 - Oosthuizen, Gerhard J. J. (Scientia Militaria - South African Journal of Military Studies, 2014)
The South African Defence Force (SADF) supported UNITA during Operation Modular (June to December 1987) to stop an extensive FAPLA offensive, known as Operation Saludando a Octubre (‘Salute October’). FAPLA and its Cuban–Russian allies intended to eliminate the ‘UNITA problem’ once and for all, and they set the conquest of Mavinga and Jamba as their first target. The SADF–UNITA alliance was, however, able to stop this advance during the Battle of the Lomba River (3 October 1987) successfully, and thereby achieved the first objective of Operation Modular. The remaining phases of Operation Modular (October to December 1987) were unsuccessfully aimed at the primary objective, namely to destroy the FAPLA brigades east of the Cuito River, or at least to force them west, across the Cuito River. The SADF–UNITA allies therefore agreed to continue military operations in the Sixth Military Region in an attempt to achieve this goal. After Operation Modular had formally come to an end early in December 1987, the planning of follow-up Operation Hooper was continued in all earnest. This article focuses on the claim of General Jannie Geldenhuys, head of the SADF (1985–1990), that Operation Hooper was an unqualified success and also on his controversial claim that Operation Hooper entered its last phase with successful attacks by the UNITA–SADF forces on 13 January, and 14 and 25 February 1988. Only the offensive/battle of 14 February 1988 was a success, however, and the SADF–UNITA alliance was unable to destroy the FAPLA brigades east of the Cuito River or to force them across the river at least. Thus, once again, not all the objectives pursued after Operation Modular could be achieved. Within a period of approximately two weeks, two unsuccessful attacks were launched against Tumpo – each time from the same direction or line of approach. The FAPLA forces were very well entrenched and equipped, and they furthermore dominated the air. In contrast, factors such as inadequate intelligence (particularly regarding the second minefield and the death acres), insufficient military equipment and manpower, inadequate logistics operations and the almost impassable sandy and bushy terrain hampered the SADF–UNITA attacks.